2015
DOI: 10.1007/s11069-015-1892-6
|View full text |Cite
|
Sign up to set email alerts
|

Flood risk assessment for urban water system in a changing climate using artificial neural network

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The potential impacts of future climate change on current urban drainage systems have received increasing attention during recent decades because of the devastating impacts of urban flooding on the economy and society (Chang et al, 2013;Zhou et al, 2012;Abdellatif et al, 2015). However, few studies have explored the role of both climate change mitigation and drainage adaptations in coping with urban flooding in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impacts of future climate change on current urban drainage systems have received increasing attention during recent decades because of the devastating impacts of urban flooding on the economy and society (Chang et al, 2013;Zhou et al, 2012;Abdellatif et al, 2015). However, few studies have explored the role of both climate change mitigation and drainage adaptations in coping with urban flooding in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the design of drainage systems is often based on historical precipitation statistics for a certain period of time, without considering the potential changes in precipitation extremes for the designed return periods (Yazdanfar and Sharma, 2015;Peng et al, 2015;Zahmatkesh et al, 2015). It is likely that drainage systems would be over-whelmed by additional runoff induced by climate change, which may lead to increased flood frequency and magnitude, disruption of transportation systems, and increased health risks (Chang et al, 2013;Abdellatif et al, 2015). For example, Arnbjerg-Nielsen (2012) reported that the design intensities in Denmark are projected to increase by 10-50 % for return periods ranging from 2 to 100 years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent year, more and more studies on the improvement/adaptation of existing drainage systems in response to climate change have emerged (Chang et al, 2013;Zhou et al, 2012;Abdellatif et al, 2015). Despite these efforts on examining the climate change impacts on urban drainage systems, limited attention has been paid to the joint analyses on urban flooding risks associated GHG mitigation and adaptation measures in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Danish design guidelines for urban drainage, a delta change of 0.3 and 0.4 are recommended for the 10and 100-year return period respectively with an anticipated technical life time of 100 years (Arnbjerg-Nielsen, 2012). The systems are likely to be overwhelmed by the additional runoff effects induced by climate change which may lead to flood damages, disruptions of transportation systems, and increased human health risks (Chang et al, 2013;Abdellatif et al, 2015). This necessitates examining the system performance in response to non-stationary changes of future hydroclimate in terms of both frequency and magnitude and the consequent flood damages (Mishra, 2015;Karamouz et al, 2013;Yazdanfar and Sharma, 2015;Notaro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ashley et al [17] analyzed the current and future pressure on planning, design, operation, and maintenance of urban drainage infrastructures in the UK. More recently, Adbellatif et al [18] carried out an assessment of climate change impact of flood risk in an urban drainage catchment located in Northwestern England, using an artificial neural network (ANN) downscaling technique to obtain local scale future rainfall from three coarse scale general circulation models (GCM). In Belgium, Willems et al [19] simulated the effects of climate change on sewer overflow frequencies using a continuous simulation reservoir-based model.…”
Section: Introductionmentioning
confidence: 99%